Evaluation of the jurisprudence course included in the book of Islamic studies for the upper classes in the light of the textbook quality standards - Ahmed Al-Qarni (Umm Al-Qura University, 2022)
This study aimed to identify the degree of observance of the Jurisprudence Course in the Islamic studies textbook for upper grades in the primary stage for standards the quality of the textbook. The researcher used the descriptive-analytical method. The research instru-ment consist of card to analyze the Jurisprudence textbooks; included eight standards and 70 indicators. The appropriate statistical methods, which were represented in calculating the stability of the analysis through Holsti's equation, averages, and percentages, were used. The study found that these textbooks characterized by their observance of textbook quality standards by 74%, which consider an average level. The elements of the book were arranged in descending order as follow: linguistic aspects (98%), then design and output element (93%), then images and illustrations element (92%), then evaluation element (97%), then element The content (83%), then the activities component (82%), then the introduction component (43%), then the objectives component, which scored zero in the verifi-cation scale because it was not included in the jurisprudence courses in the upper grades of the primary stage.